Who Avoids More? A Cross-country Evidence of Economic Policy Uncertainty and Tax Avoidance - Natania Aurielle Gunarto; Priyo Hari Adi (Universitas Pendidikan Ganesha, 2023)
Tax avoidance is a complex problem faced by governments in both developed and developing countries. This study aims to examine the effect of Uncertainty of Economic Policy (EPU) on tax avoidance and see the tendency of higher tax avoidance practices based on the level of the country's economy. This research uses a quantitative approach with an explanatory method. The study sample consisted of 21 purposively selected countries. Data was collected between 1997 and 2015. The data collection method is carried out through secondary data collection from various relevant sources, such as the UNU-WIDER Government Revenue Dataset 2021 and the EPU index of related studies. Data analysis was performed using panel data regression techniques with the help of Eviews 9 software. The results of the analysis showed a significant negative influence between EPU and tax avoidance. In addition, it was also found that developed countries have higher rates of tax avoidance than developing countries. This research provides new understanding for tax authorities in dealing with EPU in order to formulate appropriate policies to reduce tax avoidance practices. The implication of this study is the need for more effective preventive and regulatory measures in tackling tax avoidance in various countries.